2022
DOI: 10.1080/15299732.2022.2064577
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties of the adolescent dissociative experiences scale (A-DES) in a sample of Portuguese at-risk adolescents

Abstract: Dissociation is a process that often occurs as a sequela of psychological trauma, and it is interrelated with psychological and behavioral problems. In the at-risk adolescent population, dissociation is often underdiagnosed and undertreated. Having reliable measures to assess this phenomenon can help in identifying adolescents at-risk and improve treatment outcomes. This study assessed the psychometric properties of the Adolescent Dissociative Experiences Scale (A-DES) with a sample of 402 Portuguese adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Another possibility is that dissociation related to cumulative victimization and PTSD may lead to adjustment problems as a result of its association with severe emotion dysregulation. Research has shown that dissociation and emotional dysregulation are highly correlated in both adult (Hagan et al, 2015; McDonald et al, 2013) and adolescent samples (Correia-Santos, Sousa, et al, 2022; Gušić et al, 2018), although the interconnections between them are complex (e.g., Bridges-Curry et al, 2021; Ross et al, 2020). For instance, attachment insecurity is also associated with emotion dysregulation (Crow et al, 2021) and as such should also be assessed as a potential moderator (Gušić et al, 2016) or mediator (Byun et al, 2016) of the relationship between cumulative victimization and dissociation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another possibility is that dissociation related to cumulative victimization and PTSD may lead to adjustment problems as a result of its association with severe emotion dysregulation. Research has shown that dissociation and emotional dysregulation are highly correlated in both adult (Hagan et al, 2015; McDonald et al, 2013) and adolescent samples (Correia-Santos, Sousa, et al, 2022; Gušić et al, 2018), although the interconnections between them are complex (e.g., Bridges-Curry et al, 2021; Ross et al, 2020). For instance, attachment insecurity is also associated with emotion dysregulation (Crow et al, 2021) and as such should also be assessed as a potential moderator (Gušić et al, 2016) or mediator (Byun et al, 2016) of the relationship between cumulative victimization and dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation symptoms also represented an indirect effect for the link between cumulative victimization and adjustment problems. Research has shown that poly-victimized youth, besides having a higher likelihood of PTSD, also tend to report pathological levels of loss of conscious control (Correia-Santos, Sousa, et al, 2022; Kerig et al, 2016), which is a subset of the larger dissociation construct. This loss of conscious control comprises experiences of not having self-control of one’s behavior, consciousness, or thoughts, meaning emotion deregulation, which is associated with adjustment problems (Chaplo et al, 2015; Hébert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations